PERAN PENYULUH DALAM PROGRAM MODEL KAWASAN RUMAH PANGAN LESTARI (M-KRPL) DI KABUPATEN SIAK - Rabu Jalil; Cepriadi '; Kausar ' (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2015)
Model of Sustainable food house region is a house that utilizes of yard intensively through  management of local natural resources wisely which ensures of the provision of household food continuously qualified and diverse.The purpose of this research to know: (1) how much of the role of extension worker in the Model of Sustainable Food Houses Region (M-KRPL) Program: (2) What is the problems who faced by women farming group in the implementationmodel ofsustainable food houses region (M-KRPL) program. This research was conducted in Tualang village Tualang district and Sialang Baru village Lubuk Dalam district Siak Regency. This research was conducted using survey method and make observations with respondents interviewedusing a questionnaire. Any responses of respondents question was made level of the role of extension worker in the model program region sustainable food house,Scale of Liker's Summated Rating (LSR) was used,While, the data collected  of this research are primary and secondary date. In terms of analyzing the data of this research used descriptivemethod, the which one   of analysis method and filtering the data are in connecting with the theories relating of issue,in order todrawa conclusionthat ispresented. The results showedthat therole of extension workerin the model of sustainable food houseregion on Matahari KWT and Cendana Wangi KWT in the M-KRPL program were categorized as good. Theproblems faced by members ofKWTinM-KRPL programinSiakisthe meansof production, water, the opennessof the local government that existof Matahari KWT and Cendana Wangi KWT and the lack of know ledgein the agricultural cultivation. Keywords: Role of Extension, Food Crops, Model